Evaluation of Cistus ladanifer L. effect on gastrointestinal parasites in lambs - Delgado, Inês (2020)
Evaluation of Cistus ladanifer L. effect on gastrointestinal parasites in lambs Inês Delgadoa, Sara Tudela Zúquete, David Soldado, Olinda Guerreiro, Eliana Jerónimo, Ludovina Neto Padre Cistus ladanifer L. (Cistaceae) is a bountiful available shrub at the western Mediterranean region, including the south of France, Spain, Portugal and the north of Morocco. It is commonly observed in uncultivated fields. This perennial shrub contains low protein levels and high levels of phenolic compounds, such as condensed tannins (CT). It has a low organic matter digestibility, which, enhanced by its anti-nutritional components results in a poor nutritional value. However, either by natural grazing or by encouraged consumption, the incorporation of Cistus ladanifer L. in small ruminants’ diet may simultaneously act as an important feeding complement as it can transform this shrub into a high-level end-use product. With this objective, our group wanted to determine if its composition could have an influence on gastrointestinal parasites. Gastrointestinal nematode and coccidia pose as a highly significant economic burden for small ruminant production systems. Phenolic compounds, such as tannins are associated with a decrease in gastrointestinal parasites, namely, nematodes. In this study, we evaluated the effect of three levels of Cistus ladanifer CT (0, 1.25 and 2.5%) and two ways of CT supply (C. ladanifer aerial parts and C. ladanifer CT extract) on on gastrointestinal parasites in lambs. Thirty-six crossbred Merino Branco x Romane ram lambs of approximately 60 days of age were randomly assigned to individual pens (6 per dietary treatment). A total of 4 stool collections were sampled from each animal – before dietary treatment application (day 0), at the end of the adaptation period of diets (day 7), and at days 24 and 42 of the trial. Coprological techniques included nematode egg (Epg) and coccidian count by the concentration technique McMaster and all samples were also evaluated by direct microscopic observation by the Willis fluctuation method. Data was analyzed using a generalized linear mixed model procedure that identified a significant interaction of treatment groups over time regarding the strongylid Epg count (Chi2 = 85.9, p ≤ 0.001), through the Penalized Quasi-Likelihood parameter estimation method. Pairwise contrast tests, with the Holm adjustment method, showed that both ways of C. ladanifer CT supply at level of 1.25% of CT (C. ladanifer aerial parts - Chi2 = 21.7, p = 0.0006; and C. ladanifer CT extract - Chi2 = 21.4, p = 0.0006) resulted in significantly lower Epg counts of strongylids over time when compared to treatments without CT supply. This work is funded by Alentejo2020 program through the FEDER under the project CistusRumen (ALT20-030145-FEDER-000023) and by National Funds through FCT under the Project UID/AGR/00115/2019.